Cold chain management in hierarchical operational hub networks. (March 2021) - Esmizadeh, Yalda; Bashiri, Mahdi; Jahani, Hamed; Almada-Lobo, Bernardo
Highlights: Introducing a hierarchical operational hub location problem (HLP) to manage a cold chain of perishable products. Tackling a p-hub median problem with refreshing and freezing operations for hubs. Developing a genetic algorithm to solve the problem efficiently. Applying a modified Feasibility Pump Algorithm for the underlying problem. Abstract: This paper proposes a multi-objective mixed-integer linear programming to model a cold chain with complementary operations on a hierarchical hub network. Central hubs are linked to each other in the first level of the network and to the star network of the lower-level hubs. As for a case study, different hub levels provide various refreshing or freezing operations to keep the perishable goods fresh along the network. Disruption is formulated by the consideration of stochastic demand and multi-level freshness time windows. Regarding the solution, a genetic algorithm is also developed and compared for competing the large-sized networks.